Resin composition, piezoelectric material, piezoelectric film, and piezoelectric element

CN122953798APending Publication Date: 2026-10-20TDK CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580021778.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-28
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

所以,具有由现有铁电性高分子形成的压电体的压电元件,其能够使用的温度区域狭窄

Benefits of technology

[0029]本发明的树脂组合物含有:包含源自式(1)表示的偏二氰乙烯的结构单元和源自式(2)表示的乙烯酯的结构单元的偏二氰乙烯-羧酸乙烯酯共聚物;和包含葡萄糖骨架的聚合物或包含乙烯醇骨架的聚合物,因此,本发明的树脂组合物能够形成耐热性优异且相对介电常数低的压电膜,能够适合作为压电材料使用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure ZY_1
    Figure ZY_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to a resin composition comprising: a vinylidene-carboxylic acid ethylene copolymer comprising structural units derived from vinylidene cyanide represented by formula (1) and structural units derived from ethylene ester represented by formula (2); and a polymer comprising a glucose backbone or a polymer comprising a vinyl alcohol backbone, wherein the polymer comprising a glucose backbone is a cellulose ester comprising structural units derived from cellulose ester represented by formula (3) or a cellulose ether comprising structural units derived from cellulose ether represented by formula (4), and the polymer comprising a vinyl alcohol backbone is polyvinyl alcohol formaldehyde having three structural units represented by formula (5).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to resin compositions, piezoelectric materials, piezoelectric films, and piezoelectric elements.

[0002] This application claims priority based on Japanese Patent Application No. 2024-055313, filed on March 29, 2024, the contents of which are incorporated herein by reference. Background Technology

[0003] Traditionally, PZT (PbZrO3-PbTiO3 solid solution), a ceramic material, has been widely used as the piezoelectric material for forming piezoelectric elements. However, PZT has drawbacks such as lead content and brittleness due to its ceramic nature. Therefore, a material with low environmental impact and high flexibility is needed as a piezoelectric material.

[0004] As a piezoelectric material that meets these requirements, polymeric piezoelectric materials can be considered. Currently, ferroelectric polymers such as polyvinylidene fluoride (PVDF) and vinylidene fluoride-trifluoroethylene copolymer (P(VDF-TrFE)) are available as polymeric piezoelectric materials. However, these ferroelectric polymers have insufficient heat resistance. Therefore, piezoelectric materials formed from existing ferroelectric polymers lose their piezoelectric properties at high temperatures, and their elastic modulus and other physical properties deteriorate. Consequently, piezoelectric elements using piezoelectric materials formed from existing ferroelectric polymers have a narrow operating temperature range.

[0005] In addition, as piezoelectric materials, there are also amorphous polymer piezoelectric materials that achieve piezoelectricity by cooling during polarization at temperatures near their glass transition temperature (Tg). However, the piezoelectric properties of amorphous polymer piezoelectric materials disappear once they reach temperatures near their glass transition temperature. Therefore, there is a need for an amorphous polymer piezoelectric material with a high glass transition temperature and good heat resistance.

[0006] Examples of amorphous polymeric piezoelectric materials with high glass transition temperatures include vinylidene dicyanide-vinyl acetate copolymer (P(VDCN-VAc)) (see, for example, Patent Document 1).

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: International Publication No. 1991 / 013922 Summary of the Invention

[0010] The technical problem that the invention aims to solve

[0011] However, since vinylidene cyanide-vinyl carboxylate copolymers have nitrile groups (-CN, cyano) as polar groups, piezoelectric films containing this copolymer have the disadvantage of high relative permittivity.

[0012] The present invention was made in view of the above circumstances, and its object is to provide a resin composition that can form a piezoelectric film with excellent heat resistance and low relative permittivity and is suitable for use as a piezoelectric material.

[0013] Furthermore, the present invention aims to provide a piezoelectric material comprising the resin composition of the present invention, which can produce a piezoelectric film with excellent heat resistance and a low relative permittivity.

[0014] Furthermore, the present invention aims to provide a piezoelectric film comprising the piezoelectric material of the present invention, having excellent heat resistance and a low relative permittivity, and a piezoelectric element having the piezoelectric film of the present invention.

[0015] Technical solutions for solving technical problems

[0016] To address the aforementioned technical problems, the following technical solutions are provided.

[0017] The resin composition of one embodiment of the present invention comprises:

[0018] A copolymer of vinylidene-carboxylic acid esters comprising structural units derived from vinylidene cyanide represented by formula (1) below and structural units derived from ethylene esters represented by formula (2) below; and

[0019] Polymers containing a glucose backbone or polymers containing a vinyl alcohol backbone,

[0020] The polymers containing the glucose backbone described above are cellulose esters containing structural units derived from cellulose esters represented by formula (3) below, or cellulose ethers containing structural units derived from cellulose ethers represented by formula (4) below.

[0021] The polymer containing the vinyl alcohol backbone described above is a polyvinyl alcohol formaldehyde having three structural units represented by the following formula (5).

[0022]

[0023]

[0024] In equation (2), R 1 Organic groups or hydrogen atoms having 1 to 15 carbon atoms;

[0025] In equation (3), there are 3 R's. 2 They are either hydrogen atoms or carboxylic acid ester groups, with 3 Rs. 2 At least one of them is a carboxylic acid ester group;

[0026] In equation (4), there are 3 R's. 3 They are either hydrogen atoms or aliphatic ether groups, with 3 Rs. 3At least one of them is an aliphatic ether group;

[0027] In equation (5), R 4 It is a carboxylic acid ester group.

[0028] The effects of the invention

[0029] The resin composition of the present invention contains: a vinylidene-carboxylic acid ethylene ester copolymer comprising structural units derived from vinylidene cyanide represented by formula (1) and structural units derived from ethylene ester represented by formula (2); and a polymer comprising a glucose backbone or a polymer comprising an ethylene alcohol backbone. Therefore, the resin composition of the present invention can form a piezoelectric film with excellent heat resistance and low relative permittivity, and is suitable for use as a piezoelectric material. Detailed Implementation

[0030] In order to solve the above-mentioned technical problems, the inventors of the present invention focused on vinylidene cyanide-vinyl carboxylate copolymer as a piezoelectric material with high glass transition temperature (Tg) and good heat resistance, and conducted repeated and in-depth research as shown below.

[0031] First, the inventors of this invention considered forming a piezoelectric film with a relatively low permittivity by using a resin composition containing both vinylidene cyanide-vinyl carboxylate and other polymers.

[0032] To date, however, no polymers compatible with vinylidene cyanide-vinyl carboxylate copolymers are known, let alone polymers that can form piezoelectric films with relatively low permittivity by being used with vinylidene cyanide-vinyl carboxylate copolymers.

[0033] Therefore, the inventors of this invention have repeatedly studied the relative permittivity of various polymers when they are formed into sheets.

[0034] Generally, for those skilled in the art, in order to form a piezoelectric film with a lower relative permittivity than that formed from a vinylidene cyanide-vinyl carboxylate copolymer, it is generally not considered to use a polymer with a higher relative permittivity when formed in sheet form than that formed from a vinylidene cyanide-vinyl carboxylate copolymer with the vinylidene cyanide-vinyl carboxylate copolymer.

[0035] Surprisingly, it was found that by using a polymer containing a specific glucose backbone or a specific vinyl alcohol backbone, with a relative permittivity equal to or greater than that of a piezoelectric film formed from a specific vinylidene cyanide-vinyl carboxylate copolymer, together with the specific vinylidene cyanide-vinyl carboxylate copolymer, a piezoelectric film with a low relative permittivity can be formed. That is, the present invention finds that a sheet formed using a resin composition containing a specific vinylidene cyanide-vinyl carboxylate copolymer and a polymer containing a specific glucose backbone or a polymer containing a specific vinyl alcohol backbone has a lower relative permittivity compared to a piezoelectric film composed of a vinylidene cyanide-vinyl carboxylate copolymer contained in the resin composition, and a sheet composed of a polymer containing a glucose backbone or a polymer containing a vinyl alcohol backbone contained in the resin composition.

[0036] The reason for this inference is that the hydroxyl groups and / or water molecules contained in polymers containing a specific glucose backbone or polymers containing a specific vinyl alcohol backbone form hydrogen bonds with the cyano groups of a specific vinylidene cyanide-vinyl carboxylate copolymer, thereby reducing the mobility of the cyano groups of the specific vinylidene cyanide-vinyl carboxylate copolymer.

[0037] Furthermore, the inventors of this invention have demonstrated that by forming a piezoelectric film using a resin composition comprising a specific vinylidene cyanide-vinyl carboxylate copolymer and a polymer comprising a specific glucose backbone or a polymer comprising a specific vinyl alcohol backbone, a piezoelectric film with a relatively low permittivity can be obtained compared to other piezoelectric films formed similarly, except by using materials that do not contain a polymer comprising a specific glucose backbone or a polymer comprising a specific vinyl alcohol backbone, thus completing this invention.

[0038] The present invention includes the following technical solutions.

[0039] [1] A resin composition comprising: a vinylidene-vinyl carboxylate copolymer containing structural units derived from vinylidene cyanide represented by formula (1) and structural units derived from ethylene esters represented by formula (2); and

[0040] Polymers containing a glucose backbone or polymers containing a vinyl alcohol backbone,

[0041] The polymers containing the glucose backbone described above are cellulose esters containing structural units derived from cellulose esters represented by formula (3) below, or cellulose ethers containing structural units derived from cellulose ethers represented by formula (4) below.

[0042] The polymer containing the vinyl alcohol backbone described above is a polyvinyl alcohol formaldehyde having three structural units represented by the following formula (5).

[0043]

[0044]

[0045] In equation (2), R 1 Organic groups or hydrogen atoms having 1 to 15 carbon atoms;

[0046] In equation (3), there are 3 R's. 2 They are either hydrogen atoms or carboxylic acid ester groups, with 3 Rs. 2 At least one of them is a carboxylic acid ester group;

[0047] In equation (4), there are 3 R's. 3 They are either hydrogen atoms or aliphatic ether groups, with 3 Rs. 3 At least one of them is an aliphatic ether group;

[0048] In equation (5), R 4 It is a carboxylic acid ester group.

[0049] [2] According to the resin composition of [1], wherein the carboxylic acid ester group of the above formula (3) is any one or more selected from -C(=O)CH3, -C(=O)CH2CH3, -C(=O)CH2CH2CH3, -C(=O)CH(CH3)2, and the group represented by the following formula (3-1),

[0050] .

[0051] [3] According to the resin composition of [1] or [2], wherein the aliphatic ether group of the above formula (4) is any one or more groups selected from -O-CH3, -O-CH2CH2-OH and -OCH2CHOHCH3.

[0052] [4] The resin composition according to any one of [1] to [3], wherein the R of the above formula (5) is... 4 It is -C(=O)CH3.

[0053] [5] The resin composition according to any one of [1] to [4], wherein, relative to the total mass of the above-mentioned vinylidene cyanide-vinyl carboxylate copolymer and the above-mentioned polymer containing glucose backbone or the above-mentioned polymer containing vinyl alcohol backbone, the content of the above-mentioned polymer containing glucose backbone or the above-mentioned polymer containing vinyl alcohol backbone is 0.5% by mass or more and 15% by mass or less.

[0054] [6] A piezoelectric material, wherein the piezoelectric material comprises any one of the resin compositions described in any one of [1] to [5] above.

[0055] [7] A piezoelectric film, wherein the piezoelectric film comprises any one of the resin compositions described in any one of [1] to [5] above.

[0056] [8] A piezoelectric element, wherein the piezoelectric element has: [7] the piezoelectric film, and electrodes respectively disposed on one side and the other side of the piezoelectric film.

[0057] The resin composition, piezoelectric material, piezoelectric film, and piezoelectric element of the present invention will be described in detail below.

[0058] [Resin composition, piezoelectric material]

[0059] In this embodiment, an example will be given of using the resin composition of the present invention as a piezoelectric material that serves as a piezoelectric film material.

[0060] The piezoelectric material (resin composition) of this embodiment contains: a copolymer of vinylidene cyanide and ethylene carboxylate; and a polymer containing a glucose backbone or a polymer containing an ethylene alcohol backbone.

[0061] (ethylene-vinyl chloride copolymer)

[0062] The piezoelectric material of this embodiment contains a vinylidene cyanide-vinyl carboxylate copolymer comprising a structural unit derived from vinylidene cyanide (hereinafter sometimes referred to as the "first structural unit") represented by formula (1) and a structural unit derived from ethylene ester (hereinafter sometimes referred to as the "second structural unit") represented by formula (2). The vinylidene cyanide-vinyl carboxylate copolymer contained in the piezoelectric material of this embodiment may be only one type or may be two or more types.

[0063] In the piezoelectric material of this embodiment, the arrangement order of the first and second structural units, which are repeating units, in the vinylidene cyanide-vinyl carboxylate copolymer is not particularly limited. Therefore, the aforementioned vinylidene cyanide-vinyl carboxylate copolymer can be, for example, an alternating copolymer in which the first and second structural units are arranged alternately, a random copolymer in which the first and second structural units are arranged in a disordered manner, or a block copolymer having a block arrangement portion in which the first and second structural units are arranged in a continuous manner.

[0064] The piezoelectric material of this embodiment contains a vinylidene cyanide-vinyl carboxylate copolymer in which the first structural unit containing C-CN dipoles, together with the second structural unit, forms a molecular chain with a large dipole moment. Furthermore, the aforementioned vinylidene cyanide-vinyl carboxylate copolymer has a high glass transition temperature (Tg). Therefore, the piezoelectric constant d of the piezoelectric material of this embodiment containing the aforementioned vinylidene cyanide-vinyl carboxylate copolymer is [insert value here]. 33It has a sufficiently high piezoelectric value, good piezoelectric properties, and can form a coating with good heat resistance, making it suitable as a material for piezoelectric films.

[0065] In the second structural unit contained in the above-mentioned vinylidene cyanide-vinyl carboxylate copolymer, R 1 These are organic groups with 1 to 15 carbon atoms or hydrogen atoms. The above-mentioned vinylidene cyanide-vinyl carboxylate copolymers may contain R in the molecule. 1 The same second structural unit, which has only one type, can also contain R. 1 Different and various second structural units.

[0066] In the piezoelectric material of this embodiment, the R of the above-mentioned vinylidene cyanide-vinyl carboxylate copolymer 1 Since the R¹ group consists of organic groups with 1 to 15 carbon atoms or hydrogen atoms, the volume of R¹ will not become excessively large, making it easy to ensure the volume ratio of the first structural unit containing the C-CN dipole in the molecule. As a result, it is easy to obtain a piezoelectric film with high piezoelectric properties by means of a coating containing the piezoelectric material of this embodiment through polarization treatment.

[0067] In R 1 In the case of an organic group having 1 to 15 carbon atoms, as R 1 Examples include: alkyl groups with 1 to 15 carbon atoms that can have substituents; aromatic cyclic groups that can have substituents; phosphonic acid groups that can have substituents; heterocyclic groups that can have substituents; and aliphatic cyclic groups that can have substituents. As R 1 Substituents that can be present when these groups are fluorinated, chlorolated, halogenated, nitrile, alkyl, etc.

[0068] In R 1 When the alkyl group having 1 to 15 carbon atoms can have substituents, it is used as R. 1 Examples of linear alkyl groups with 1 to 15 carbon atoms include: dichloromethyl, trichloromethyl, difluoromethyl, trifluoromethyl, 2-cyanoethyl, isobutyl, tert-butyl, 2-ethylhexyl, and 2-(acetylacetoxy)ethyl. Examples of linear alkyl groups with 1 to 15 carbon atoms include methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, and n-pentadecanyl.

[0069] In R 1 In the case of aromatic cyclic groups that can have substituents, as R 1 Examples include: phenyl, 2-methylphenyl, 3-methylphenyl, 4-methylphenyl, 4-tert-butylphenyl, 4-nitrophenyl, 4-cyanophenyl, naphthyl, etc.

[0070] In R 1 In the case of phosphonic acid groups that can have substituents, as R 1 Examples include: dimethylphosphonomethyl, diethylphosphonomethyl, diphenylphosphonomethyl, etc.

[0071] In R 1 In the case of heterocyclic groups that can have substituents, as R 1 Examples include: furfuryl, tetrahydrofuryl, 2-oxotetrahydrofuran-3-yl, 4-methyl-2-oxotetrahydro-2H-pyran-4-yl, etc.

[0072] In R 1 In the case of aliphatic cyclic groups that can have substituents, as R 1 Examples include: 1-adamantyl, 2-methyl-2-adamantyl, 2-ethyl-2-adamantyl, 2-isopropyl-2-adamantyl, isobornyl, dicyclopentyl, etc.

[0073] Among these groups, R 1 Preferably, it is a straight-chain alkyl group having 1 to 3 carbon atoms, and particularly preferably a methyl group. When R 1 When R is a straight-chain alkyl group with 1 to 3 carbon atoms, 1 The smaller volume makes it easier to ensure a higher volume ratio of the first structural unit containing C-CN dipoles in the molecule. As a result, coatings containing the piezoelectric material comprising the aforementioned vinylidene cyanide-vinyl carboxylate copolymer can easily yield piezoelectric films with further enhanced piezoelectric properties through polarization treatment.

[0074] The piezoelectric material of this embodiment may also contain one or more structural units other than the first and second structural units, as needed, in the form of a vinylidene cyanide-vinyl carboxylate copolymer. Examples of other structural units include structural units derived from known monomers or oligomers having polymerizable unsaturated bonds.

[0075] In the copolymer of vinylidene cyanide and ethylene carboxylate, the total content of the first structural unit and the second structural unit is preferably 80% by mass or more, because it becomes a piezoelectric material capable of forming a coating with even better piezoelectric properties and heat resistance. The total content of the first structural unit and the second structural unit is more preferably 90% by mass or more, and most preferably only the first structural unit and the second structural unit.

[0076] In the piezoelectric material of this embodiment, the content of the second structural unit in the vinylidene cyanide-vinyl carboxylate copolymer is preferably 95 to 105 mol relative to 100 mol of the first structural unit, which is a repeating unit. When the content of the second structural unit is 95 mol or more relative to 100 mol of the first structural unit, it is possible to suppress the excessive C-CN dipoles in the molecule, which could lead to excessively high molecular polarity. Therefore, the piezoelectric film formed using the piezoelectric material of this embodiment has a lower relative permittivity. When the content of the second structural unit is 105 mol or less relative to 100 mol of the first structural unit, it is easy to ensure the volume ratio of the first structural unit containing C-CN dipoles in the molecule. As a result, the coating containing the piezoelectric material of this embodiment can easily yield a piezoelectric film with high piezoelectric properties through polarization treatment.

[0077] The weight-average molecular weight (Mw) of the vinylidene cyanide-vinyl carboxylate copolymer contained in the piezoelectric material of this embodiment is preferably 10,000 to 1,000,000. When the weight-average molecular weight (Mw) of the copolymer is 10,000 or more, the film-forming properties become very good, and it is easy to manufacture a piezoelectric film containing the piezoelectric material of this embodiment. In addition, when the weight-average molecular weight (Mw) of the copolymer is 1,000,000 or less, the compatibility with polymers containing a glucose backbone or polymers containing a vinyl alcohol backbone becomes better, and by mixing with polymers containing a glucose backbone or polymers containing a vinyl alcohol backbone, a piezoelectric material that can be easily and efficiently manufactured is obtained.

[0078] The weight-average molecular weight (Mw) of the vinylidene cyanide-vinyl carboxylate copolymer in this embodiment is a value obtained by the method shown below.

[0079] Under the measurement conditions shown below, the weight-average molecular weight (Mw) of the vinylidene cyanide-vinyl carboxylate copolymer was measured using a liquid chromatograph (LC-2050C; manufactured by Shimadzu Corporation). The weight-average molecular weight (Mw) was determined by comparison with the following standard substances with known molecular weights.

[0080] <Measurement Conditions>

[0081] Chromatographic column: 3 TSKgel α-M (manufactured by Tosoh Corporation) in series

[0082] Mobile phase solvent: N,N-dimethylformamide (DMF) (with 10 mM LiBr added)

[0083] Flow rate: 1.0 ml / min

[0084] Column temperature: 40℃

[0085] Standard materials: polyethylene glycol, polyethylene oxide (PEG, PEO) (manufactured by Tosoh Corporation, Scientific Polymer Products, Inc., Agilent Technologies)

[0086] The vinylidene cyanide-vinyl carboxylate copolymer contained in the piezoelectric material of this embodiment can be manufactured by existing known methods. Specifically, for example, it can be manufactured by free radical copolymerization of raw material monomers containing vinylidene cyanide and vinyl esters having corresponding second structural units using a polymerization initiator such as azobisisobutyronitrile (AIBN) and a known method.

[0087] (Polymers containing a glucose backbone or polymers containing a vinyl alcohol backbone)

[0088] The piezoelectric material of this embodiment contains either a polymer containing a glucose backbone or a polymer containing a vinyl alcohol backbone.

[0089] The piezoelectric material of this embodiment contains a polymer with a glucose backbone that is a cellulose ester containing a structural unit derived from the cellulose ester shown in formula (3) (hereinafter sometimes referred to as the "third structural unit") or a cellulose ether containing a structural unit derived from the cellulose ether shown in formula (4) (hereinafter sometimes referred to as the "fourth structural unit").

[0090] The piezoelectric material of this embodiment contains a polymer with a vinyl alcohol backbone, which is polyvinyl alcohol formaldehyde having three structural units as shown in formula (5).

[0091] The piezoelectric material of this embodiment may contain only one type of polymer with a glucose backbone or two or more types of polymer with a vinyl alcohol backbone.

[0092] (cellulose ester)

[0093] When the polymer containing the glucose backbone is a cellulose ester containing a third structural unit, the third structural unit contained in the polymer containing the glucose backbone has 3 R... 2 They are either hydrogen atoms or carboxylic acid ester groups, with 3 Rs. 2 At least one of them is a carboxylic acid ester group. (3 Rs) 2 The number of carboxylic acid ester groups contained therein can be 2 or 3 R. 2 All are carboxylic acid ester groups. The three R groups in the third structural unit... 2 When the number of carboxylic acid ester groups contained is 2 or 3, the types of carboxylic acid ester groups contained in each third structural unit can be different, or they can be partially or completely the same.

[0094] Furthermore, when the polymer containing the glucose backbone is a cellulose ester containing a third structural unit, the number of carboxylic acid ester groups in the multiple third structural units contained in the polymer containing the glucose backbone may be different or partially or completely the same.

[0095] In the case where the polymer containing the glucose backbone in the piezoelectric material of this embodiment is a cellulose ester containing a third structural unit, the polymer containing the glucose backbone is preferably R in the molecule. 2 The proportion of carboxylic acid ester groups in the molecule is 20% by mass or more, more preferably 30% to 95% by mass. This is because when R in the molecule 2 When the proportion of carboxylic acid ester groups in the quantity is 20% or more by mass, due to the carboxylic acid ester portion contained in the vinylidene cyanide-vinyl carboxylate copolymer (-OC(=O)-R in formula (2)) 1 The high affinity between the glucose backbone and the carboxylic acid ester groups in polymers further improves the compatibility with vinylidene cyanide-vinyl carboxylate copolymers. Furthermore, this is also because when R in the molecule... 2 When the proportion of carboxylic acid ester groups in the polymer is less than 95% by mass, the hydroxyl groups in the polymer containing the glucose backbone form hydrogen bonds with the cyano groups in the vinylidene cyanide-vinyl carboxylate copolymer, thereby becoming a piezoelectric material capable of forming a coating with an even lower relative permittivity.

[0096] Examples of carboxylic acid ester groups contained in the third structural unit include: -C(=O)CH3, -C(=O)CH2CH3, -C(=O)CH2CH2CH3, -C(=O)CH(CH3)2, and groups shown in formula (3-1) below. Preferably, the carboxylic acid ester group contained in the third structural unit is selected from any one or two or more of -C(=O)CH3, -C(=O)CH2CH3, -C(=O)CH2CH2CH3, and -C(=O)CH(CH3)2. This is because it has a high affinity for the carboxylic acid ester portion contained in the vinylidene cyanide-vinyl carboxylate copolymer, resulting in better compatibility with the vinylidene cyanide-vinyl carboxylate copolymer.

[0097]

[0098] Furthermore, when the polymer containing the glucose backbone is a cellulose ester containing a third structural unit, the types of carboxylic acid ester groups in the multiple third structural units contained in the polymer containing the glucose backbone may be different or partially or completely the same.

[0099] In the case where the polymer containing the glucose backbone in the piezoelectric material of this embodiment is a cellulose ester containing a third structural unit, the polymer containing the glucose backbone may, as needed, contain one or more structural units other than the third structural unit. Examples of other structural units include, for instance, the three R units in the structural unit shown in formula (3). 2 All of them are structural units composed of hydrogen atoms.

[0100] When the polymer containing the glucose backbone is a cellulose ester containing a third structural unit, the content of the third structural unit in the polymer containing the glucose backbone is preferably 80% by mass or more. This is because it becomes a piezoelectric material capable of forming a coating with a further low relative permittivity and further good piezoelectric properties. The content of the third structural unit is more preferably 90% by mass or more, and most preferably only the third structural unit.

[0101] In the case where the polymer containing the glucose backbone in the piezoelectric material of this embodiment is a cellulose ester containing a third structural unit, the weight-average molecular weight (Mw) of the polymer containing the glucose backbone is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000. When the weight-average molecular weight (Mw) of the polymer containing the glucose backbone is 10,000 or more, the film-forming properties become better, and it is easy to manufacture a piezoelectric film containing the piezoelectric material of this embodiment. When the weight-average molecular weight (Mw) of the polymer containing the glucose backbone is 1,000,000 or less, the compatibility with the vinylidene cyanide-vinyl carboxylate copolymer becomes better. Therefore, piezoelectric materials containing polymers containing the glucose backbone with a weight-average molecular weight (Mw) of 1,000,000 or less can be manufactured efficiently with good productivity.

[0102] In the case where the polymer containing the glucose backbone is a cellulose ester containing a third structural unit, the weight-average molecular weight (Mw) of the polymer containing the glucose backbone in this embodiment is a value measured by the method shown below.

[0103] Under the measurement conditions shown below, the weight-average molecular weight (Mw) of polymers containing a glucose backbone was measured using a liquid chromatograph (LC-2050C; manufactured by Shimadzu Corporation). The weight-average molecular weight (Mw) was determined by comparison with the following standard substances with known molecular weights.

[0104] <Measurement Conditions>

[0105] Chromatographic column: TSKgel guardcolumn α+TSKgel α-M (manufactured by Tosoh Corporation)

[0106] Mobile phase solvent: N-methyl-2-pyrrolidone (NMP) (with 10 mM LiBr added)

[0107] Flow rate: 1.0 ml / min

[0108] Column temperature: 40℃

[0109] Standard material: TSK Standard Polystyrene (manufactured by Tosoh Corporation)

[0110] In the case where the polymer containing the glucose backbone in the piezoelectric material of this embodiment is a cellulose ester containing a third structural unit, the cellulose ester can be manufactured by existing known methods such as the reaction of organic acid anhydrides with cellulose, or commercially available products can be used.

[0111] Commercially available cellulose esters include, for example: cellulose acetate butyrate (model 180963; manufactured by Aldrich), cellulose triacetate (model 22199; manufactured by Aldrich), cellulose triacetate (model 035-16761; manufactured by Fujifilm and Wako Pure Chemical Industries), cellulose acetate propionate (model 340642; manufactured by Aldrich), and cellulose acetate (model 419028; manufactured by Aldrich).

[0112] Cellulose acetate butyrate (model 180963; manufactured by Aldrich) has a weight-average molecular weight of 250,000 and contains -C(=O)CH3 and -C(=O)CH2CH2CH3 as carboxylic acid ester groups. The molecule contains R of formula (3). 2 Of the total amount, -C(=O)CH3 accounted for 28.0% to 31.0% by mass, and -C(=O)CH2CH2CH3 accounted for 16.5% to 19.0% by mass.

[0113] Cellulose triacetate (model 22199; manufactured by Aldrich) has a weight-average molecular weight of 340,000 and only has -C(=O)CH3 as a carboxylic acid ester group. The molecule contains R of formula (3). 2 The proportion of carboxylic acid ester groups in the quantity is 100 by mass.

[0114] Cellulose triacetate (model 035-16761; manufactured by Fujifilm and Koh Genuine Chemicals Co., Ltd.) has a weight-average molecular weight of 310,000 and only has -C(=O)CH3 as a carboxylic acid ester group. The molecule contains R of formula (3). 2 The proportion of carboxylic acid ester groups in the quantity is 100 by mass.

[0115] Cellulose acetate propionate (model 340642; manufactured by Aldrich) has a weight-average molecular weight of 36,000 and contains -C(=O)CH3 and -C(=O)CH2CH3 as carboxylic acid ester groups. The molecule contains R of formula (3). 2 Of the total amount, -C(=O)CH3 accounts for 0.0% to 1.0% by mass, and -C(=O)CH2CH3 accounts for 40% to 45% by mass.

[0116] Cellulose acetate (model 419028; manufactured by Aldrich) has a weight-average molecular weight of 194,000 and only has -C(=O)CH3 as a carboxylic acid ester group. The molecule contains R of formula (3). 2 Of the total amount, the proportion of carboxylic acid ester groups is 39.7% by mass.

[0117] (cellulose ether)

[0118] When the polymer containing the glucose backbone is a cellulose ether containing a fourth structural unit, in the fourth structural unit contained in the polymer containing the glucose backbone, there are 3 R... 3 They are either hydrogen atoms or aliphatic ether groups, with 3 Rs. 3 At least one of them is an aliphatic ether group. (3 Rs) 3 The number of aliphatic ether groups contained therein can be 2 or 3 R groups. 2 All are aliphatic ether groups. The three R groups in the fourth structural unit... 3 When the number of aliphatic ether groups contained in the structure is 2 or 3, the types of aliphatic ether groups contained in each fourth structural unit can be different, or they can be partially or completely the same.

[0119] Furthermore, when the polymer containing the glucose backbone is a cellulose ether containing a fourth structural unit, the number of aliphatic ether groups in the multiple fourth structural units contained in the polymer containing the glucose backbone may be different or partially or completely the same.

[0120] In the case where the polymer containing the glucose backbone in the piezoelectric material of this embodiment is a cellulose ether containing a fourth structural unit, the polymer containing the glucose backbone is preferably R in the molecule. 3 The proportion of aliphatic ether groups in the molecule is 20% by mass or more, more preferably 30% to 95% by mass. This is because when R in the molecule 3 When the proportion of aliphatic ether groups in the quantity is 20% or more by mass, due to the carboxylic acid ester portion (equation (2) of the vinylidene cyanide-vinyl carboxylate copolymer) contained in the copolymer, the -OC(=O)-R 1The high affinity between the polymer and the aliphatic ether groups contained in the glucose backbone further improves the compatibility with vinylidene cyanide-vinyl carboxylate copolymers. Furthermore, this is also because when R in the molecule... 3 When the proportion of aliphatic ether groups in the polymer is less than 95% by mass, hydrogen bonds are formed between the hydroxyl groups in the polymer containing the glucose backbone and the cyano groups in the vinylidene cyanide-vinyl carboxylate copolymer, thereby creating a piezoelectric material capable of forming a coating with an even lower relative permittivity.

[0121] Examples of aliphatic ether groups included in the fourth structural unit include groups represented by -O-CH3, -O-CH2CH2-OH, and -OCH2CHOHCH3. Preferably, the aliphatic ether group in the fourth structural unit is selected from any one or more of -O-CH3 and -OCH2CHOHCH3. This is because they have a high affinity for the carboxylic acid ester portion of the vinylidene cyanide-vinyl carboxylate copolymer, resulting in better compatibility with the copolymer.

[0122] Furthermore, when the polymer containing the glucose backbone is a cellulose ether containing a fourth structural unit, the types of aliphatic ether groups possessed by the multiple fourth structural units contained in the polymer containing the glucose backbone may be different or partially or completely the same.

[0123] In the case where the polymer containing the glucose backbone in the piezoelectric material of this embodiment is a cellulose ether containing a fourth structural unit, the polymer containing the glucose backbone may, as needed, contain one or more structural units other than the fourth structural unit. Examples of other structural units include, for instance, the three R units in the structural unit shown in formula (4). 3 All of them are structural units composed of hydrogen atoms.

[0124] When the polymer containing the glucose backbone is a cellulose ether containing a fourth structural unit, the content of the fourth structural unit in the polymer containing the glucose backbone is preferably 80% by mass or more. This is because it becomes a piezoelectric material capable of forming a coating with a further low relative permittivity and further good piezoelectric properties. The content of the fourth structural unit is more preferably 90% by mass or more, and most preferably only the fourth structural unit.

[0125] In the case where the polymer containing the glucose backbone in the piezoelectric material of this embodiment is a cellulose ether containing a fourth structural unit, the weight-average molecular weight (Mw) of the polymer containing the glucose backbone is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000. When the weight-average molecular weight (Mw) of the polymer containing the glucose backbone is 10,000 or more, the film-forming properties become better, and it is easier to manufacture a piezoelectric film containing the piezoelectric material of this embodiment. When the weight-average molecular weight (Mw) of the polymer containing the glucose backbone is 1,000,000 or less, the compatibility with the vinylidene cyanide-vinyl carboxylate copolymer becomes better. Therefore, piezoelectric materials containing polymers containing the glucose backbone with a weight-average molecular weight (Mw) of 1,000,000 or less can be manufactured efficiently with good productivity.

[0126] In the case where the polymer containing the glucose backbone is a cellulose ether containing a fourth structural unit, the weight-average molecular weight (Mw) of the polymer containing the glucose backbone in this embodiment is a value measured by the method shown below.

[0127] Under the measurement conditions shown below, the weight-average molecular weight (Mw) of polymers containing a glucose backbone was measured using a liquid chromatograph (LC-2050C; manufactured by Shimadzu Corporation). The weight-average molecular weight (Mw) was determined by comparison with the following standard substances with known molecular weights.

[0128] <Measurement Conditions>

[0129] Chromatographic column: TSKgel guardcolumn α+TSKgel α-M (manufactured by Tosoh Corporation)

[0130] Mobile phase solvent: N-methyl-2-pyrrolidone (NMP) (with 10 mM LiBr added)

[0131] Flow rate: 1.0 ml / min

[0132] Column temperature: 40℃

[0133] Standard material: TSK Standard Polystyrene (manufactured by Tosoh Corporation)

[0134] In the case where the polymer containing the glucose backbone in the piezoelectric material of this embodiment is a cellulose ether containing a fourth structural unit, the cellulose ether can be manufactured by existing known methods such as contacting cellulose with an alkaline solution to form alkali cellulose and then performing an etherification reaction using an etherifying agent, or commercially available products can also be used.

[0135] Commercially available cellulose ethers include, for example, methylcellulose (model SM-15; manufactured by Shin-Etsu Chemical Industry) and hydroxypropyl methylcellulose (model 60SH-50; manufactured by Shin-Etsu Chemical Industry).

[0136] (Polyvinyl formaldehyde)

[0137] In the case where the polymer containing the vinyl alcohol backbone is a polyvinyl alcohol formaldehyde having the three structural units shown in formula (5), R 4 It is a carboxylic acid ester group.

[0138] This is because, in the case where the polymer containing the ethylene alcohol backbone in the piezoelectric material of this embodiment is polyvinyl alcohol formaldehyde having three structural units as shown in formula (5), the carboxylic acid ester portion (in formula (2) of the vinylidene cyanide-vinyl carboxylic acid copolymer) contains the carboxylic acid ester portion (in formula (2) of the -OC(=O)-R) 1 The high affinity between the polyvinyl alcohol backbone and the carboxylic acid ester groups contained in the polymer further improves the compatibility with vinylidene cyanide-vinyl carboxylate copolymers. Furthermore, since the polymer containing the polyvinyl alcohol backbone is a polyvinyl alcohol formaldehyde having the three structural units shown in formula (5), and the R in formula (5) contains... 4 Since it is a carboxylic acid ester group, it forms hydrogen bonds with the cyano groups of the vinylidene cyanide-vinyl carboxylic acid ester copolymer through the hydroxyl groups contained in the polymer containing the vinyl alcohol backbone, thus becoming a piezoelectric material capable of forming coatings with even lower relative permittivity.

[0139] Examples of carboxylic acid ester groups contained in polyvinyl formal include -C(=O)CH3. This is because they have a high affinity for the carboxylic acid ester portion of the vinylidene cyanide-vinyl carboxylate copolymer, resulting in better compatibility with the vinylidene cyanide-vinyl carboxylate copolymer.

[0140] In the case where the polymer containing the ethylene alcohol backbone in the piezoelectric material of this embodiment is polyvinyl alcohol formaldehyde having the three structural units shown in formula (5), the weight-average molecular weight (Mw) of the polymer containing the ethylene alcohol backbone is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000. When the weight-average molecular weight (Mw) of the polymer containing the ethylene alcohol backbone is 10,000 or more, the film-forming properties become better, and it is easy to manufacture a piezoelectric film containing the piezoelectric material of this embodiment. When the weight-average molecular weight (Mw) of the polymer containing the ethylene alcohol backbone is 1,000,000 or less, the compatibility with vinylidene cyanide-vinyl carboxylate copolymer becomes better. Therefore, piezoelectric materials containing polymers containing the ethylene alcohol backbone with a weight-average molecular weight (Mw) of 1,000,000 or less can be manufactured efficiently with good productivity.

[0141] In the case where the polymer containing the vinyl alcohol backbone is a polyvinyl alcohol formaldehyde having the three structural units shown in formula (5), the weight-average molecular weight (Mw) of the polymer containing the vinyl alcohol backbone in this embodiment is a value measured by the method shown below.

[0142] Under the measurement conditions shown below, the weight-average molecular weight (Mw) of polymers containing a vinyl alcohol backbone was measured using a liquid chromatograph (LC-2050C; manufactured by Shimadzu Corporation). The weight-average molecular weight (Mw) was determined by comparison with the following standard substances with known molecular weights.

[0143] <Measurement Conditions>

[0144] Chromatographic column: TSKgel guardcolumn α+TSKgel α-M (manufactured by Tosoh Corporation)

[0145] Mobile phase solvent: N-methyl-2-pyrrolidone (NMP) (with 10 mM LiBr added)

[0146] Flow rate: 1.0 ml / min

[0147] Column temperature: 40℃

[0148] Standard material: TSK Standard Polystyrene (manufactured by Tosoh Corporation)

[0149] In the case where the polymer containing the ethylene alcohol backbone in the piezoelectric material of this embodiment is polyvinyl alcohol formaldehyde having three structural units as shown in formula (5), polyvinyl alcohol formaldehyde can be manufactured by existing known methods such as the method of performing a formaldehyde reaction on polyvinyl alcohol obtained by hydrolysis of polyvinyl acetate using formaldehyde, or commercially available products can be used.

[0150] Commercially available polyvinyl alcohol formaldehyde (PVA) products include, for example, polyvinyl alcohol formaldehyde (model Vinyleck-K; manufactured by JNC).

[0151] In the piezoelectric material of this embodiment, the content of the polymer containing a glucose backbone or the polymer containing a vinylidene cyanide-vinyl carboxylate copolymer is preferably 0.5% by mass or more and 15% by mass or less, more preferably 1% by mass or more and 5% by mass or less, relative to the total mass of the polymer containing a glucose backbone or the polymer containing a vinylidene alcohol backbone. When the content of the polymer containing a glucose backbone or the polymer containing a vinylidene alcohol backbone is 1% by mass or more, the effect of reducing the relative permittivity of the piezoelectric film containing the piezoelectric material due to the polymer containing a glucose backbone or the polymer containing a vinylidene alcohol backbone becomes significant. When the content of the polymer containing a glucose backbone or the polymer containing a vinylidene alcohol backbone is 15% by mass or less, the reduction in the piezoelectric properties of the piezoelectric film containing the piezoelectric material due to excessive content of the polymer containing a glucose backbone or the polymer containing a vinylidene alcohol backbone can be suppressed, and a voltage output g can be formed. 33 High-value piezoelectric films.

[0152] The content of the vinylidene cyanide-vinyl carboxylate copolymer and the content of the polymer containing a glucose backbone or the polymer containing a vinyl alcohol backbone in the piezoelectric material of this embodiment can be calculated from the results of analysis of the piezoelectric material using known analytical methods. As an analytical method, for example, a selection from... 1 H-NMR (nuclear magnetic resonance) analysis, 13 One or more of the following: C-NMR analysis, gas chromatography-mass spectrometry (GC-MS) analysis, etc.

[0153] Furthermore, the content of the vinylidene cyanide-vinyl carboxylate copolymer and the content of polymers containing a glucose backbone or a vinyl alcohol backbone in the piezoelectric material can be calculated by analyzing the components extracted from the piezoelectric material using known extraction methods. For example, extraction methods can be employed using organic solvents such as chloroform or dichloroethane that do not dissolve the vinylidene cyanide-vinyl carboxylate copolymer to extract polymers containing a glucose backbone or polymers containing a vinyl alcohol backbone from the piezoelectric material.

[0154] The piezoelectric material of this embodiment can contain one or more polymers and / or copolymers other than the aforementioned vinylidene-vinyl carboxylate copolymer, polymer containing a glucose backbone, and polymer containing a vinyl alcohol backbone, depending on the heat resistance and strength of the piezoelectric film containing the piezoelectric material and the characteristics of the coating solution used to form the piezoelectric film containing the piezoelectric material by a coating method. Preferably, these other polymers and / or copolymers are compatible with the aforementioned vinylidene-vinyl carboxylate copolymer, polymer containing a glucose backbone, and polymer containing a vinyl alcohol backbone.

[0155] In the piezoelectric material of this embodiment, the total content of the polymers and copolymers contained in the above-mentioned vinylidene cyanide-vinyl carboxylate copolymer and the polymer containing a glucose backbone or the polymer containing a vinyl alcohol backbone is preferably 80% by mass or more, more preferably 90% by mass or more, and most preferably only the above-mentioned vinylidene cyanide-vinyl carboxylate copolymer and the polymer containing a glucose backbone or the polymer containing a vinyl alcohol backbone.

[0156] In the case of manufacturing piezoelectric films using a coating method, the piezoelectric material of this embodiment preferably contains a solvent in order to prepare a coating solution that is easy to coat. As solvents, known solvents such as acetonitrile, dimethylformamide, dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolium ketone, 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, dihydro-L-glucanone, γ-butyrolactone, γ-valerolactone, ethylene carbonate, propylene carbonate, and hexamethylphosphoric triamine can be used. These solvents can be used alone or in mixtures of two or more.

[0157] In addition to the aforementioned vinylidene cyanide-vinyl carboxylate copolymer, polymer containing a glucose backbone, and polymer containing a vinyl alcohol backbone, the piezoelectric material of this embodiment may contain known additives as needed. Examples of additives include various antioxidants, hydrolysis inhibitors, fillers, surface modifiers, thixotropic agents, etc.

[0158] [Method for manufacturing piezoelectric materials (resin compositions)]

[0159] The piezoelectric material (resin composition) of this embodiment can be manufactured, for example, by mixing raw materials consisting of the above-mentioned vinylidene cyanide-vinyl carboxylate copolymer, the above-mentioned polymer containing a glucose backbone or polymer containing a vinyl alcohol backbone, and other polymers and / or copolymers other than the above-mentioned vinylidene cyanide-vinyl carboxylate copolymer, the above-mentioned polymer containing a glucose backbone or polymer containing a vinyl alcohol backbone, additives, and solvents as needed.

[0160] When manufacturing the piezoelectric material of this embodiment, the method for mixing raw materials can be, for example, a known method such as a magnetic stirrer, a mechanical stirrer, or a rotary mixer.

[0161] [Piezoelectric film]

[0162] The piezoelectric film of this embodiment comprises the piezoelectric material (resin composition) of this embodiment.

[0163] The piezoelectric film of this embodiment can be manufactured, for example, by the following method: The piezoelectric material (resin composition) of this embodiment is coated to a peelable substrate to form a coating film. Known substrates such as resin films can be used as the substrate. The coating method for the piezoelectric material can be any known method, depending on the coating thickness and the viscosity of the piezoelectric material. Then, the coating film is dried to remove the solvent, thus producing a piezoelectric material sheet. The piezoelectric material sheet can also be stretched as needed.

[0164] Next, a piezoelectric material sheet is peeled off from the substrate, and electrodes made of a known conductive material such as aluminum are placed on one and the other sides of the piezoelectric material sheet. Then, a voltage is applied to the piezoelectric material sheet with a certain electric field strength via the electrodes on both sides, at a certain polarization temperature near the glass transition temperature (Tg) of the piezoelectric material forming the piezoelectric material sheet. Then, the piezoelectric material sheet is cooled while maintaining the applied voltage. This imparts piezoelectricity to the piezoelectric material sheet. Through the above processes, a sheet-like piezoelectric film is obtained.

[0165] The electrodes used to obtain piezoelectricity can be used directly as components for forming piezoelectric elements, or they can be removed.

[0166] [Piezoelectric element]

[0167] The piezoelectric element of this embodiment includes a piezoelectric film as described in this embodiment, and electrodes respectively disposed on one side and the other side of the piezoelectric film. Specifically, a piezoelectric element having a sheet-like piezoelectric film and electrodes respectively disposed on one side and the other side of the piezoelectric film can be cited as an example. As the material of the electrodes, known conductive materials such as aluminum can be used.

[0168] The piezoelectric element of this embodiment can be manufactured, for example, by setting electrodes on one side and the other side of the piezoelectric film using known methods such as vapor deposition.

[0169] The piezoelectric material (resin composition) of this embodiment contains: a vinylidene-vinyl carboxylate copolymer comprising structural units derived from vinylidene cyanide as shown in formula (1) and structural units derived from vinyl ester as shown in formula (2); and a polymer comprising a glucose backbone, i.e., a cellulose ester comprising structural units derived from cellulose ester as shown in formula (3) or a cellulose ether comprising structural units derived from cellulose ether as shown in formula (4), or a polymer comprising a vinyl alcohol backbone, i.e., polyvinyl alcohol formaldehyde having three structural units as shown in formula (5). Therefore, a piezoelectric film with excellent heat resistance and low relative permittivity can be formed, making it suitable for use as a piezoelectric material.

[0170] Furthermore, the piezoelectric film of this embodiment includes the piezoelectric material of this embodiment. Therefore, the piezoelectric film and the piezoelectric element of this embodiment have excellent heat resistance and excellent piezoelectric properties.

[0171] The embodiments of the present invention have been described in detail above. However, the structures and combinations thereof in each embodiment are merely examples. Without departing from the spirit of the present invention, structures may be added, omitted, replaced, or otherwise modified.

[0172] For example, in the above embodiments, the case of using the resin composition as a piezoelectric material is described as an example, but the use of the resin composition of the present invention is not limited to piezoelectric materials.

[0173] Example

[0174] (Manufacturing of piezoelectric materials)

[0175] [Examples 1 to 57, Comparative Examples 1 to 17]

[0176] According to the proportions shown in Table 1, the vinylidene cyanide-vinyl carboxylate copolymers shown in Tables 1 to 4, the added resin varieties shown in Table 1, and dimethylformamide as a solvent were mixed by stirring with a magnetic stirrer to prepare piezoelectric materials of Examples 1 to 57 and Comparative Examples 1 to 17.

[0177] The following polymers are used as the copolymers of vinylidene cyanide-vinyl carboxylate shown in Tables 1 to 4, and as the added resin varieties.

[0178] Furthermore, the content of the added resin varieties shown in Tables 1 to 4 is the content relative to the total mass of the polymer contained in the piezoelectric materials of Examples 1 to 57 and Comparative Examples 1 to 17.

[0179] In Tables 1 to 4, the polymers contained in the piezoelectric materials refer to vinylidene cyanide-vinyl carboxylate copolymers, polymers used as alternatives to vinylidene cyanide-vinyl carboxylate copolymers, cellulose esters containing structural units derived from cellulose esters represented by formula (3), cellulose ethers containing structural units derived from cellulose ethers represented by formula (4), polyvinyl alcohol formaldehyde, polycarbonate, polyamide imide, and polyimide having three structural units represented by formula (5).

[0180] (ethylene-vinyl chloride copolymer)

[0181] As a vinylidene cyanide-vinyl carboxylate copolymer, the following is used <11> ~ <15> copolymers.

[0182] <11> The R in formula (2) contained in the molecule 1All are methyl groups, consisting only of a first structural unit and a second structural unit, with the same molar ratio of the first and second structural units, and a weight-average molecular weight (Mw) of 580,000.

[0183] <12> The R in formula (2) contained in the molecule 1 All are ethyl, consisting only of a first structural unit and a second structural unit, with the same molar ratio of the first structural unit to the second structural unit, and a weight-average molecular weight (Mw) of 297,000.

[0184] <13> The R in formula (2) contained in the molecule 1 All are propyl, consisting only of a first structural unit and a second structural unit, with the same molar ratio of the first and second structural units, and a weight-average molecular weight (Mw) of 480,000.

[0185] <14> The R in formula (2) contained in the molecule 1 It consists of methyl and propyl groups, with a molar ratio of methyl to propyl of 1:1. It is composed only of a first structural unit and a second structural unit, with the first and second structural units having the same molar ratio. The weight-average molecular weight (Mw) is 341,000.

[0186] <15> The R in formula (2) contained in the molecule 1 All are tert-butyl, consisting only of a first structural unit and a second structural unit, with the same molar ratio between the first and second structural units, and a weight-average molecular weight (Mw) of 304,000.

[0187] <16> In Comparative Example 7, instead of vinylidene cyanide-vinyl carboxylate copolymer, the polymer of Formula (1) was used; 99% by mass of the polymer composed of structural units derived from vinylidene cyanide as shown in Formula (1) was used as the polymer.

[0188] <17> In Comparative Example 8, instead of the vinylidene cyanide-vinyl carboxylate copolymer, the polymer of formula (2) was used; the vinyl ester derived from formula (2) (R in formula (2)) was used. 1 Polymers composed of methyl (polyvinyl acetate; 189480, Sigma-Aldrich) are used as polymers at 99% mass.

[0189] (Added resin varieties)

[0190] Cellulose esters containing structural units derived from the cellulose esters shown in formula (3):

[0191] As a cellulose ester containing structural units derived from the cellulose ester shown in formula (3), the following polymers shown in Tables 1 to 4 are used.

[0192] • Cellulose acetate butyrate (model 180963, manufactured by Aldrich) (weight average molecular weight (Mw): 250,000)

[0193] • Cellulose triacetate (model 22199, manufactured by Aldrich) (weight-average molecular weight (Mw): 340,000)

[0194] • Cellulose acetate (model 419028, manufactured by Aldrich) (weight average molecular weight (Mw): 194,000)

[0195] Cellulose ethers comprising structural units derived from the cellulose ethers shown in formula (4) below:

[0196] As a cellulose ether containing a structural unit derived from the cellulose ether shown in formula (4), the following polymers shown in Tables 1 to 4 are used.

[0197] • Methylcellulose (model SM-15, manufactured by Shin-Etsu Chemical Co., Ltd.) (weight average molecular weight (Mw): 56,400)

[0198] • Hydroxypropyl methylcellulose (1) (Model 60SH-50, manufactured by Shin-Etsu Chemical Industry) (Weight-average molecular weight (Mw): 94,700)

[0199] • Hydroxypropyl methylcellulose (2) (Model 65SH-50, manufactured by Shin-Etsu Chemical Co., Ltd.) (Weight-average molecular weight (Mw): 103,000)

[0200] • Hydroxypropyl methylcellulose (3) (Model 90SH-100, manufactured by Shin-Etsu Chemical Industry) (Weight-average molecular weight (Mw): 133,000)

[0201] Polyvinyl alcohol formaldehyde as shown in formula (5):

[0202] As polyvinyl alcohol formaldehyde as shown in formula (5), the following polymers shown in Tables 1 to 4 are used.

[0203] • Polyvinyl alcohol formaldehyde (model Vinyleck-K, manufactured by JNC) (weight average molecular weight (Mw): 19,900)

[0204] Other polymers:

[0205] The following polymers shown in Table 1 are used as polymers other than cellulose esters containing structural units derived from cellulose esters of formula (3), cellulose ethers containing structural units derived from cellulose ethers of formula (4), and polyvinyl alcohol formaldehyde having three structural units as shown in formula (5).

[0206] • Polycarbonate; Model PCZ-200, manufactured by Mitsubishi Gas Chemical Company

[0207] • Polyamide-imide; Model HR11NN, manufactured by Toyobo Co., Ltd.

[0208] • Polyimide; KPI-MX300F, manufactured by Kawamura Industrial Co., Ltd.

[0209] [Table 1]

[0210]

[0211] [Table 2]

[0212]

[0213] [Table 3]

[0214]

[0215] [Table 4]

[0216]

[0217] (Manufacturing of piezoelectric films)

[0218] [Examples 1 to 57, Comparative Examples 1 to 17]

[0219] Piezoelectric films were manufactured using the piezoelectric materials of Examples 1 to 57 and Comparative Examples 1 to 17, respectively, by the method shown below.

[0220] A piezoelectric material is coated onto a PET film (trade name: Lumirror (registered trademark), manufactured by Toray Industries, Inc.) as a substrate, to a thickness of 50 μm after drying, forming a coating film. Then, the coating film formed on the PET film is dried on a heating plate at 120°C for 6 hours to remove the solvent from the coating film, obtaining a piezoelectric material sheet.

[0221] The obtained piezoelectric material sheet was peeled off from the PET film, and aluminum electrodes were deposited on one and the other sides of the piezoelectric material sheet by vapor deposition. Then, a high-voltage power supply device HARB-20R60 (manufactured by Matsus Advrecision Co., Ltd.) was electrically connected to the electrodes of the piezoelectric material sheet, and the sheet was held at a polarization temperature of 165°C for 15 minutes under an applied electric field strength of 80 MV / m. Then, the sheet was slowly cooled to room temperature while maintaining the applied voltage to perform polarization treatment, resulting in a sheet-like piezoelectric film.

[0222] The appearance of the piezoelectric films of Examples 1 to 57 and Comparative Examples 1 to 17 obtained as described above was visually observed, and their compatibility was evaluated according to the criteria shown below. The results are shown in Tables 1 to 4.

[0223] [Evaluation Criteria]

[0224] A (Compatible): The piezoelectric film is transparent.

[0225] B (Incompatible): The piezoelectric film becomes cloudy.

[0226] As shown in Tables 1 to 3, in Examples 1 to 48, which contain vinylidene cyanide-vinyl carboxylate copolymer and the polymer of the present invention containing a glucose backbone or a polymer containing a vinyl alcohol backbone, the compatibility evaluation was A, and a piezoelectric material of the mixture of the two polymers was obtained.

[0227] Furthermore, as shown in Table 1, the compatibility evaluation of Comparative Example 8, which includes the polymer of Formula (2) and cellulose acetate butyrate, was also A, resulting in a piezoelectric material composed of the two polymers.

[0228] Furthermore, as shown in Table 4, the compatibility evaluation of Examples 49 to 57, which contain vinylidene cyanide-vinyl carboxylate copolymer and the polymer of the present invention containing a glucose backbone or a polymer containing a vinyl alcohol backbone, was also A, resulting in a piezoelectric material composed of two polymers.

[0229] However, the compatibility evaluations of Comparative Example 4 (containing vinylidene cyanide-vinyl carboxylate copolymer and polycarbonate), Comparative Example 5 (containing vinylidene cyanide-vinyl carboxylate copolymer and polyamide-imide), and Comparative Example 6 (containing vinylidene cyanide-vinyl carboxylate copolymer and polyimide) were all B, and a piezoelectric material containing the mixture of the two polymers could not be obtained. Furthermore, as shown in Table 1, the compatibility evaluation of Comparative Example 7 (containing the polymer of formula (1) and cellulose acetate butyrate) was also B, and a piezoelectric material containing the mixture of the two polymers could not be obtained.

[0230] It should be noted that the piezoelectric materials of Comparative Examples 1, 14, 15, 16, and 17 contained only vinylidene cyanide-vinyl carboxylate copolymer as polymers, without any added resins, and therefore no compatibility evaluation was conducted.

[0231] In addition, the piezoelectric materials of Comparative Examples 2 to 3 and Comparative Examples 9 to 13 only contained added resin varieties as polymers and did not mix with vinylidene cyanide-vinyl carboxylate copolymer, so no compatibility evaluation was conducted.

[0232] In addition, the relative permittivity and piezoelectric constant d of the piezoelectric films of Examples 1 to 57 and Comparative Examples 1 to 17 were determined by the methods shown below. 33 The voltage output g was measured and calculated. 33 The results are shown in Tables 5 to 8.

[0233] It should be noted that, since Comparative Examples 4 to 7, which had a compatibility rating of B and failed to produce sheet-like piezoelectric films by mixing the two polymers, were not subjected to tests involving relative permittivity and piezoelectric constant d, these tests were not conducted. 33 Voltage output g 33 Evaluation.

[0234] (Methods for measuring relative permittivity)

[0235] The electrostatic capacitance of the piezoelectric film was measured at room temperature under conditions of 1.00 V and 1 kHz using an LCR meter (ZM2372, manufactured by NF Circuit Design Co., Ltd.). Furthermore, the thickness of the piezoelectric film was measured at room temperature using a dial indicator (ID-C112XB, manufactured by Mitutoyo Co., Ltd.). Then, the dielectric constant was calculated using the measured values ​​of the electrostatic capacitance and the piezoelectric film thickness to determine the relative dielectric constant.

[0236] (piezoelectric constant d) 33 (Measurement method)

[0237] A needle with a tip diameter of 1.5 mm was used as a sample holder to assemble the piezoelectric film onto the measuring device. The piezoelectric constant d... 33 The measuring device used was the PIEZOTEST PM200 piezoelectric system.

[0238] piezoelectric constant d 33 The measured value is positive or negative depending on whether the piezoelectric film is on the front or back. In this specification, the absolute value of the measured value is recorded as the piezoelectric constant d. 33 The value of .

[0239] (Voltage output g) 33 (Calculation method)

[0240] The voltage output g is calculated using the following formula. 33 .

[0241] Voltage output g 33 (mVm / N) = piezoelectric constant d 33 (pC / N) / Relative Permittivity

[0242] [Table 5]

[0243]

[0244] [Table 6]

[0245]

[0246] [Table 7]

[0247]

[0248] [Table 8]

[0249]

[0250] As shown in Tables 5-8, the piezoelectric films of Examples 1-57, which were manufactured using the piezoelectric materials of Examples 1-57, had a lower relative permittivity compared to the piezoelectric films of Comparative Examples 1, 14-17, which were manufactured using the piezoelectric materials of Comparative Examples 1, 14-17, which contained only a single polymer or copolymer.

[0251] Furthermore, the piezoelectric films of Examples 1-10 and 13-48, manufactured using the piezoelectric materials of Examples 1-10 and 13-48 (where the content of the polymer containing the glucose backbone or the polymer containing the vinyl alcohol backbone of the present invention is 15% by mass or less), have a voltage output g compared to the piezoelectric films of Examples 11-12 and 49-57 (where the content of the polymer containing the glucose backbone or the polymer containing the vinyl alcohol backbone of the present invention exceeds 15% by mass). 33 Relatively high.

[0252] Furthermore, as shown in Table 5, the piezoelectric film of Comparative Example 8, manufactured using the piezoelectric material of Comparative Example 8 that does not contain vinylidene cyanide-vinyl carboxylate copolymer, failed to polarize, and the piezoelectric constant d could not be measured. 33 The voltage output g could not be calculated either. 33 .

[0253] It should be noted that the materials in Comparative Examples 2-3 and 9-13 did not contain vinylidene cyanide-vinyl carboxylate copolymer. The films of Comparative Examples 2-3 and 9-13 manufactured using these materials failed to obtain piezoelectric properties and piezoelectric bodies, therefore the piezoelectric constant d could not be measured. 33 The voltage output g could not be calculated either. 33 .

Claims

1. A resin composition, wherein, The resin composition contains: A copolymer of vinylidene-carboxylic acid esters comprising structural units derived from vinylidene cyanide represented by formula (1) below and structural units derived from ethylene esters represented by formula (2) below; and Polymers containing a glucose backbone or polymers containing a vinyl alcohol backbone, The polymer containing the glucose backbone is a cellulose ester containing structural units derived from a cellulose ester represented by formula (3) below, or a cellulose ether containing structural units derived from a cellulose ether represented by formula (4) below. The polymer containing the vinyl alcohol backbone is a polyvinyl alcohol formaldehyde having three structural units represented by the following formula (5). In equation (2), R 1 Organic groups or hydrogen atoms having 1 to 15 carbon atoms; In equation (3), there are 3 R's. 2 They are either hydrogen atoms or carboxylic acid ester groups, with 3 Rs. 2 At least one of them is a carboxylic acid ester group; In equation (4), there are 3 R's. 3 They are either hydrogen atoms or aliphatic ether groups, with 3 Rs. 3 At least one of them is an aliphatic ether group; In equation (5), R 4 It is a carboxylic acid ester group.

2. The resin composition according to claim 1, wherein, The carboxylic acid ester group in formula (3) is selected from any one or more of the groups represented by -C(=O)CH3, -C(=O)CH2CH3, -C(=O)CH2CH2CH3, -C(=O)CH(CH3)2, and the group represented by formula (3-1) below. 。 3. The resin composition according to claim 1, wherein, The aliphatic ether group in formula (4) is any one or more of the groups represented by -O-CH3, -O-CH2CH2-OH, and -OCH2CHOHCH3.

4. The resin composition according to claim 1, wherein, The R in equation (5) 4 It is -C(=O)CH3.

5. The resin composition according to claim 1, wherein, The content of the polymer containing the glucose backbone or the polymer containing the vinylidene cyanide-vinyl carboxylate copolymer is 0.5% by mass or less and 15% by mass relative to the total mass of the polymer containing the glucose backbone or the polymer containing the vinyl alcohol backbone.

6. A piezoelectric material, wherein, The piezoelectric material comprises the resin composition according to any one of claims 1 to 5.

7. A piezoelectric film, wherein, The piezoelectric film comprises the resin composition according to any one of claims 1 to 5.

8. A piezoelectric element, wherein, The piezoelectric element comprises: the piezoelectric film as described in claim 7, and electrodes respectively disposed on one side and the other side of the piezoelectric film.

Citation Information

Patent Citations

  • Vinylidene cyanide alternating copolymers

    WO1991013922A1